2012
DOI: 10.3171/2012.3.jns11706
|View full text |Cite
|
Sign up to set email alerts
|

Timing of clinical grade assessment and poor outcome in patients with aneurysmal subarachnoid hemorrhage

Abstract: Timing of WFNS grade assessment affects its prognostic value. Outcome after aneurysmal SAH is best predicted by assessing WFNS grade after neurological resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 8 publications
(7 reference statements)
2
32
1
Order By: Relevance
“…8,14 This notion is corroborated by our data. Up to now, hydrocephalus has been thought to be the main confounder interfering with grading in patients with SAH.…”
Section: Seizures and Timing Of Grading In Patients With Sahsupporting
confidence: 82%
See 1 more Smart Citation
“…8,14 This notion is corroborated by our data. Up to now, hydrocephalus has been thought to be the main confounder interfering with grading in patients with SAH.…”
Section: Seizures and Timing Of Grading In Patients With Sahsupporting
confidence: 82%
“…7 Neurological resuscitation included intubation and mechanical ventilation for airway protection or, if respiratory distress developed, placement of arterial and venous lines, a CSF diversion via an external ventricular drain (EVD) or lumbar drain in case of hydrocephalus, and initiation of antiepileptic drugs (AEDs) after reported seizure, with administration of parenteral fluids to maintain euvolemia and initiation of nimodipine on admission. 8 In cases in which the patient's Glasgow Coma Scale (GCS) score could not be assessed due to continued sedation, the last GCS score before intubation was used. Patients were dichotomized into good-grade (WFNS I-III) and poor-grade (WFNS IV-V) groups.…”
Section: Methodsmentioning
confidence: 99%
“…4 Although a good clinical grade was definitely the strongest factor associated with greater chances of excellent outcome in our cohort, we also found that nearly onethird of patients who presented with poor clinical grade were able to reach an excellent recovery. These numbers are higher than those reported in a previous study, which found that 16% of poor-grade patients who underwent aneurysm treatment had an MRS score of 0-1 at 1 year.…”
Section: Discussionmentioning
confidence: 65%
“…8,35,36,42 Some researchers have also argued about the optimal time point for assessing neurological status for purposes of prognostication, with different time points proposed in the literature, including clinical assessment soon after injury, 4 and after neurological resuscitation. 12 Third, because the study is not population based, there is the potential that we systematically underestimated the magnitude of prognostic associations, as patients who died prior to hospital admission were not accounted for. Furthermore, the data were weighted toward trial patients.…”
Section: Discussionmentioning
confidence: 99%